2015
DOI: 10.1590/0037-8682-0043-2015
|View full text |Cite
|
Sign up to set email alerts
|

Presence of anti-Leishmania (Viannia) braziliensis antibodies in blood donors in the West-Central region of the State of Paraná, Brazil

Abstract: Introduction: Serological screening in blood banks does not include all transmittable diseases. American cutaneous leishmaniasis (ACL) has a high detection rate in the municipalities of the State of Paraná. Methods: This study analyzed the presence of antiLeishmania braziliensis antibodies in 176 blood donors who live in these endemic areas. The variables were analyzed with the χ 2 test and Stata 9.1 software. Results: Twenty (11.4%) samples were positive for the presence of anti-L. braziliensis antibodies. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Prior large studies, including from our group, have found striking differences in the prevalence of VL within different regions in Brazil, as well as Southern Europe. The highest seroprevalence was observed in Mato Grosso, 41.40% of blood donors, in contrast to other regions in Brazil [Salvador: 5.40% of 700 (Fukutani et al, 2014); Paraná: 11.40% of 176 (Braga et al, 2015); Fortaleza: 17.10% of 431 (Monteiro et al, 2016)], and in Southern Europe [France: 13.40% of 565 (le Fichoux et al, 1999); Spain: 3.10% of 1,437 (França et al, 2018)].…”
Section: Discussionmentioning
confidence: 90%
“…Prior large studies, including from our group, have found striking differences in the prevalence of VL within different regions in Brazil, as well as Southern Europe. The highest seroprevalence was observed in Mato Grosso, 41.40% of blood donors, in contrast to other regions in Brazil [Salvador: 5.40% of 700 (Fukutani et al, 2014); Paraná: 11.40% of 176 (Braga et al, 2015); Fortaleza: 17.10% of 431 (Monteiro et al, 2016)], and in Southern Europe [France: 13.40% of 565 (le Fichoux et al, 1999); Spain: 3.10% of 1,437 (França et al, 2018)].…”
Section: Discussionmentioning
confidence: 90%
“…Prior large studies, including from our group, have found striking differences in the prevalence of VL within different regions in Brazil, as well as Southern Europe. The highest seroprevalence was observed in Mato Grosso, 41.40% of blood donors, in contrast to other regions in Brazil (Salvador: 5.40% of 700 [60]; Paraná: 11.40% of 176 [65]; Fortaleza: 17.10% of 431 [66]), and in Southern Europe (France: 13.40% of 565 [67]; Spain: 3.10% of 1,437 [68]).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is known that L. braziliensis DNA can be detected in blood samples of animals and humans 25,26 . The possibility that L. braziliensis could be transmitted via blood transfusion has been speculated 19 , but remains unproven.…”
Section: Discussionmentioning
confidence: 99%